Lean training in manufacturing company - Koay, Phaik Ai; Nordin, Norani (2015)
The demanding of the product with high variety is increasing with the need of lower cost, short lead time, and good quality has led to the implementation of lean manufacturing which also to eliminate waste in a company.Lean training is needed to implement lean production in a company. This study attempts to explore how a manufacturing company carry out lean training, identify the types of lean training applies in training worker, and identify the constraints face by company during lean training.This study is focus on manufacturing company that has lean department in Malaysia.The data was collected via qualitative method which is an in-depth interview and analyzed by manual method. The results shows that lean training should involve both off-the-job training and on-the-job training.The limitation of the study is lack of literature related with lean training in manufacturing company.Future research might expand their research to other industry such as lean training in service industry.